PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB BERFITUR AUDIO PADA MATERI HEWAN HERBIVORA UNTUK SISWA SDLB-A DI SLB PGRI KALITIDU - Amir, Day Ramadhani; Abelianti, Nurlita; Amin, Ahmad Kholiqul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students who are blind require educational aids that cater to their specific learning characteristics, particularly by leveraging their sense of hearing. Observations and interviews at SLB PGRI Kalitidu revealed that support teachers rely on Braille books, verbal explanations, and YouTube audio content to teach science. These tools are not yet integrated into a single platform designed to meet the specific learning needs of visually impaired students. However, teachers noted that two students at the school (SDLB-A) possess good hearing abilities, making audio-based media a viable option for their learning activities. This study aimed to develop a web-based learning medium featuring audio named